Expanding oxygen minimum zones in the northern Indian Ocean predicted by hypoxia-related bacteria - Liu, Jinyan; Cui, Zhisong; Luan, Xiao; Wang, Zongling; Zhang, Xuelei (Frontiers in Marine Science, 2024)
Oxygen minimum zones (OMZs) in the ocean are areas with dissolved oxygen (DO) concentrations below critical thresholds that impact marine ecosystems and biogeochemical cycling. In the northern Indian Ocean (NIO), OMZs exhibit a tendency to expand in mesopelagic waters and contribute significantly to global nitrogen loss and climate change. However, the microbial drivers of OMZ expansion in the NIO remain understudied. Here, we characterized bacterial communities across DO gradients in the NIO using high-throughput 16S rRNA gene sequencing. We found that Marinimicrobia, Chloroflexi, and the SAR324 clade were enriched in both oxygen-deficient and low oxygen mesopelagic waters. Furthermore, Marinimicrobia, Chloroflexi, and the SAR324 clade exhibited a significant negative correlation with DO (P < 0.01), suggesting that they were well-adapted to the oxygen-deficient OMZ habitat. Functional predictions revealed heightened nitrogen metabolism in OMZs, particularly nitrate reduction, suggesting its pivotal role in nitrogen loss. These findings underscore the importance of microbial communities in driving OMZ expansion in the NIO and highlight their implications in global biogeochemical cycles and climate change.